The Role of Sociological and Pedagogical Foundations in Islamic Education Management - Yuli Umro'atin; Asrop Syafi'i; Roberto Charlos; Rahmatullah Abd Ahmed (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
The presence of Islamic education management is the right solution to realizing real education, as described in the Qur'an and Hadith, apart from being a philosophy it can also be realized in real educational historical practice to create independent and creative individuals. This research goals to explain the Sociological and Pedagogical foundations in Islamic education management, a long with urgency of the Sociological and Pedagogical foundations in Islamic Education Management. This study uses a literature study in which all results and discussions are sourced from books and journal articles. The results and discussion include: One of the principles in the foundation of Islamic Education Management is the principle of society, namely the understanding that humans are social beings, not individuals. Management of Islamic Education from pedagogical perspective in Islam is prepared to create a generation that is capable, independent.